FRRS1L variants and ferriheme overload drive hyperpigmentation and systemic Iron overload in lanping black bone sheep - Deping Han; Yuanyuan Zhang; Weidong Deng; Xue Yang; Jianfei Chen; Guoying Hua; Hesham Y.A. Darwish; Huaming Mao; Xiao Gou; Jiankui Wang; Kai Cui; Yuhao Ma; et al. (Cell & Bioscience)
Abstract Background Hemoglobin metabolism disorder can result in systemic iron overload, leading to pigmentation in multiple organs. Although these disorders are often of genetic origin, the specific genes and mechanisms remain incompletely understood. Lanping black bone sheep (LP–BBS), a unique population from the high altitudes along the Hengduan Mountains in Yunnan province, exhibits hyperpigmentation in multiple tissues. Investigating the genetic and environmental factors underlying this phenotype provides a natural model to better understand hemoglobin metabolism disorder. Results LP-BBS were found to exhibit increased red blood cell counts, elevated hemoglobin levels, and systemic iron overload, evidenced by hyperpigmentation in various tissues. Histological and molecular analyses revealed that hyperpigmentation is driven by ferriheme overload, an inheritable quantitative trait influenced by both genetic variation and environmental factors. Genome-wide association studies identified FRRS1L as a candidate gene, with significant mutations in its 3′-untranslated region (3′-UTR) reducing FRRS1L expression. Functional assays demonstrated that insufficient FRRS1L expression promotes ferriheme accumulation in reticuloendothelial cells and macrophages, as confirmed in vitro using FRRS1L knockdown models. Ferriheme overload was associated with oxidative stress and systemic inflammation, causing pathological damage to critical organs such as the kidney, liver, and uterus. Conclusion This study identifies FRRS1L as a key contributor to ferriheme overload through aberrant hemoglobin metabolism in LP–BBS. These findings offer new insights into the genetic basis and pathological mechanisms of iron overload disorders, providing a potential target for therapeutic intervention. Moreover, LP–BBS serves as a valuable natural model for studying hematogenous pigment disorders and their interplay with environmental factors.